Hand Masses - Teh, James; Shahabpour, Maryam; Drape, Jean-Luc; Feydy, Antoine; Sudoł-Szopińska, Iwona; Vanhoenacker, Filip M. (Seminars in Musculoskeletal Radiology, 2021)
Hand and wrist soft tissue masses may be classified as pseudotumors, benign neoplasms, or malignant neoplasms. The vast majority of hand lesions are benign. Consideration of the location of the lesion and its imaging characteristics often leads to a specific diagnosis. Pseudotumors discussed in this article are ganglion cysts, accessory muscles, and inflammatory lesions. True tumors are described according to their tissue type: nerve sheath tumors, adipocytic tumors, so-called fibrohistiocytic tumors, pericytic tumors, and vascular lesions. We also outline the imaging features of masses encountered in the hand and wrist.
Keywords: hand and wrist tumor; mass; magnetic resonance imaging; ultrasound